Graduación en el Teatro Melico Salazar. (UNED, 2016)
Aparece Nancy Vásquez Flores en el podio. Aparecen en la mesa principal María Graciela Núñez Núñez, Gisele Bolaños Mora, Luis Guillermo Carpio Malavasi - Rector, Ronald Bonilla Carvajal, Katya Calderón Herrera y Nelson José Briceño Vargas